Tunisia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper reviews the progress made by the Tunisian authorities in their efforts to liberalize the capital account and highlights the potential benefits of implementing the remaining reforms in this area. It also analyzes the developments within a unified analytical framework, provides tentative insights regarding priorities for the government's growth strategy ahead, and discusses the impact of ongoing labor market reforms and investment promotion policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet